The CDIO ++ Approach to University Faculty Advance Training for Research and Teaching Activities - A. I. Chuchalin (Высшее образование в России)
A review of the literature on university faculty advanced training for research and teaching activities is presented. Based on the analysis of the experience of Russian and foreign universities, the principles for developing a modern faculty advanced training system at the university are set out responding to the challenges associated with the ongoing and expected changes in the content and technology of student training, primarily in the field of STEM. It is proposed to use the CDIO ++ approach for advanced training of faculty of various categories (professor, associate professor, assistant) to research and teaching activities in the conditions of division of labor when creating and implementing educational products at various stages of their life cycle. The distribution of academic staff potential is shown and an assessment of the resources of a program for faculty advanced training is given on the basis of the CDIO ++ approach for a hypothetical university with a given structure and established priorities for faculty members of various categories.